AUTOMATIC ROUTE FINDER FOR NEW VISITORS - ADNAN, MOHD SHIHAM (Universiti Teknologi Petronas, 2006)
Shortest path finding algorithms are necessary in road network of a city or country for tourists and visitors. Automatic Route Finder tool for New Visitors is developed to help them to find or plan the shortest and effective way in order to reach their destination without loss of time. This project proposes a new visitor route model that is based on shortest path algorithms for road networks. Shortest path problems are among the best studied network flow optimization problems, with interesting applications in a range of fields. This study is based on Dijkstra's algorithm as the algorithm finds the most effective way to traverse an entire graph. The user is first need to select the starting location and the ending destination then the shortest path will be highlighted with the total distance between the two locations. If one of the roads in the first shortest path had problems, then the Automatic Route Finder will highlight the new shortest path from the two locations.